Mini viral RNAs act as innate immune agonists during influenza virus infection - te Velthuis, A; Long, J; Bauer, D; Fan, R; Yen, H; Sharps, J; Siegers, J; Killip, M; French, H; Oliva-Martín, M; Randall, R; de Wit, E; et al. (Nature Publishing Group, 2018)
The molecular processes that determine the outcome of influenza virus infection in humans are multifactorial and involve a complex interplay between host, viral and bacterial factors1. However, it is generally accepted that a strong innate immune dysregulation known as ‘cytokine storm’ contributes to the pathology of infections with the 1918 H1N1 pandemic or the highly pathogenic avian influenza viruses of the H5N1 subtype2,3,4. The RNA sensor retinoic acid-inducible gene I (RIG-I) plays an important role in sensing viral infection and initiating a signalling cascade that leads to interferon expression5. Here, we show that short aberrant RNAs (mini viral RNAs (mvRNAs)), produced by the viral RNA polymerase during the replication of the viral RNA genome, bind to and activate RIG-I and lead to the expression of interferon-β. We find that erroneous polymerase activity, dysregulation of viral RNA replication or the presence of avian-specific amino acids underlie mvRNA generation and cytokine expression in mammalian cells. By deep sequencing RNA samples from the lungs of ferrets infected with influenza viruses, we show that mvRNAs are generated during infection in vivo. We propose that mvRNAs act as the main agonists of RIG-I during influenza virus infection.